Physical and Chemical Characteristic of Halal Gelatin Extracted from Buffalo Hide with Addition of Pineapple Rind at Different Ratio - Aprizal, Aprizal; Mirdhayati, Irdha; Yendraliza, Yendraliza (UIN Sunan Gunung Djati Bandung, 2019)
The production of halal gelatin from buffalo hide waste which is animal be slaughtered according to Islamic law and using pineapple rind as an extraction agent was an alternative to produce halal gelatin. The availability of buffalo hide in Riau Province was stable and its hide had high protein content. This research was conducted to produced and determine the characteristics of halal gelatin from buffalo hide using solution of pineapple skin in terms of their physical and chemical properties. The Completely Randomized Design (CRD) was experimental design used with consist of 3 treatments and 4 replications. The treatment was ratio hide : pineapple rind solution, namely 3:1, 3:2 , 3:3 w/v. The parameters observed were yield, viscosity, color, pH, ash content and moisture content. The results showed that immersion of buffalo hide in the solution of pineapple rind at different ratio gave highly significant increased the viscosity and ash content of gelatin but not significant effect to yield percentage , color, pH and moisture of gelatin. The yield percentage ranging from 5.99-7.33%, pH 4.83-4.85, viscosity was 1.95-2.20 cP, color 0.54-0.71 absorbance unit, ash 0.25-, 032% and moisture 9.97-9.99%. It can be concluded that the best treatment was ratio 3:2 and 3 : 3 according to had viscosity, pH, color, ash and moisture in line with the standard of gelatin by Gelatin Manufacture Institute of America (GMIA).